Authentication of vegetable oils by confocal X-ray scattering analysis with coherent/incoherent scattered X-rays. (1st November 2016) - Li, Fangzuo; Liu, Zhiguo; Sun, Tianxi
Highlights: Confocal X-ray scattering was used for identifying oil samples. This approach was based on Rayleigh to Compton scattering intensity ratio. The effective atomic number of tested oils was obtained. The confocal X-ray scattering technology was based on polycapillary X-ray optics. Abstract: This paper presents an alternative analytical method based on the Rayleigh to Compton scattering intensity ratio and effective atomic number for non-destructive identification of vegetable oils using confocal energy dispersive X-ray fluorescence and scattering spectrometry. A calibration curve for the Rayleigh to Compton scattering intensity ratio and effective atomic number was constructed on the basis of a reliable physical model for X-ray scattering. The content of light elements, which are "invisible" using X-ray fluorescence, can be calculated "by difference" from the calibration curve. In this work, we demonstrated the use of this proposed approach to identify complex organic matrices in different vegetable oils with high precision and accuracy.